Genomic resolution of a cold subsurface aquifer community provides metabolic insights for novel microbes adapted to high CO2 concentrations. (7th July 2016) - Probst, Alexander J.; Castelle, Cindy J.; Singh, Andrea; Brown, Christopher T.; Anantharaman, Karthik; Sharon, Itai; Hug, Laura A.; Burstein, David; Emerson, Joanne B.; Thomas, Brian C.; Banfield, Jillian F.
Summary: As in many deep underground environments, the microbial communities in subsurface high‐CO2 ecosystems remain relatively unexplored. Recent investigations based on single‐gene assays revealed a remarkable variety of organisms from little studied phyla in Crystal Geyser (Utah, USA), a site where deeply sourced CO2 ‐saturated fluids are erupted at the surface. To provide genomic resolution of the metabolisms of these organisms, we used a novel metagenomic approach to recover 227 high‐quality genomes from 150 microbial species affiliated with 46 different phylum‐level lineages. Bacteria from two novel phylum‐level lineages have the capacity for CO2 fixation. Analyses of carbon fixation pathways in all studied organisms revealed that the Wood‐Ljungdahl pathway and the Calvin‐Benson‐Bassham Cycle occurred with the highest frequency, whereas the reverse TCA cycle was little used. We infer that this, and selection for form II RuBisCOs, are adaptions to high CO2 ‐concentrations. However, many autotrophs can also grow mixotrophically, a strategy that confers metabolic versatility. The assignment of 156 hydrogenases to 90 different organisms suggests that H2 is an important inter‐species energy currency even under gaseous CO2 ‐saturation. Overall, metabolic analyses at the organism level provided insight into the biochemical cycles that support subsurface life under the extreme condition of CO2 saturation.